Accurate space-based NOx emission estimates with the flux divergence approach require fine-scale model information on local oxidation chemistry and profile shapes - F. Cifuentes; F. Cifuentes; H. Eskes; E. Dammers; E. Dammers; C. Bryan; F. Boersma; F. Boersma (Geoscientific Model Development)
The flux divergence approach (FDA) is a popular technique for deriving NOx emission estimates from tropospheric NO2 columns measured by the TROPOspheric Monitoring Instrument (TROPOMI) satellite sensor. An attractive aspect of the FDA is that the method simplifies three-dimensional atmospheric chemistry and transport processes into a two-dimensional (longitude–latitude) steady-state continuity equation for columns that balances local NOx emissions with the net outflow and chemical loss of NOx. Here we test the capability of the FDA to reproduce known NOx emissions from synthetic NO2 column retrievals generated with the LOTOS-EUROS chemistry transport model over the Netherlands at high spatial resolution of about 2×2 km during summer. Our results show that the FDA captures the magnitude and spatial distribution of the NOx emissions to high accuracy (absolute bias <9 %), provided that the observations represent the NO2 column in the boundary layer, that wind speed and direction are representative for the boundary layer (PBL) column, and that the high-resolution spatiotemporal variability of the NO2 lifetimes and NOx:NO2 ratio is accounted for in the inversion instead of using single fixed values. The FDA systematically overestimates NOx emissions by 15 %–60 % when using tropospheric NO2 columns as the driving observation, while using PBL NO2 columns largely overcomes this systematic error. This merely reflects the fact that the local balance between emissions and sinks of NOx occurs in the boundary layer, which is decoupled from the NO2 in the free troposphere. Based on the recommendations from this sensitivity test, we then applied the FDA using observations of NO2 columns from TROPOMI, corrected for contributions from free-tropospheric NO2, between 1 June and 31 August 2018. The NOx emissions derived from the default TROPOMI retrievals are biased low over cities and industrialized areas. However, when the coarse 1×1° TM5-MP NO2 profile used in the retrieval is replaced by the high-resolution profile of LOTOS-EUROS, the TROPOMI NOx emissions are enhanced by 22 % and are in better agreement with the inventory for the Netherlands. This emphasizes the importance of using realistic high-resolution a priori NO2 profile shapes in the TROPOMI retrieval. We conclude that accurate quantitative NOx emissions estimates are possible with the FDA, but they require sophisticated, fine-scale corrections for both the NO2 observations driving the method and the estimates of the NO2 chemical lifetime and NOx:NO2 ratio. This information can be obtained from high-resolution chemistry transport model simulations at the expense of the simplicity and applicability of the FDA.